The value of metagenomic next-generation sequencing with blood samples for the diagnosis of disseminated tuberculosis - Ma, Jing; Jiang, Yongfang; He, Yan; Zhou, Huaying (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThe aim of this study was to assess the clinical value of metagenomic next-generation sequencing (mNGS) of blood samples for the identification of disseminated tuberculosis (DTB).MethodsA total of 48 individuals suspected of DTB were enrolled. All patients underwent mNGS of peripheral blood and conventional microbiological tests. Patient characteristics were collected from their medical records.ResultsA total of 28 patients were diagnosed with DTB, whereas 20 patients were confirmed as non-DTB cases. In the DTB groups, 19 (67.9%) contained TB sequences, with specific reads of TB ranging from 1 to 219. The TB sequence was more detectable by mNGS in male patients, those with elevated PCT levels, those who are HIV positive, and those with a decreased CD4 T-cell count. The HIV-positive group shows higher TB mNGS reads (p = 0.012) and TB mNGS sensitivity (p = 0.05). The sensitivity of TB mNGS in blood samples was 80% for HIV-infected patients and 44.4% for non-HIV-infected individuals (p = 0.05). The non-HIV group had a higher prevalence of miliary tuberculosis (p = 0.018), and extrapulmonary tuberculosis was more prevalent in the HIV-positive group.ConclusionOur research has shown that the mNGS of blood samples has excellent sensitivity for the diagnosis of DTB. The TB sequence was more detectable by mNGS in patients with elevated PCT levels, those who are HIV positive, and those with a decreased CD4 T-cell count.